Effect of cold isostatic pressing on the transport current of filamentary MgB2 wire made by the IMD process. (19th May 2016) - Kováč, P; Hušek, I; Pachla, W; Melišek, T; Kulich, M; Rosová, A; Kopera, L
Abstract: This work describes the effect of cold isostatic pressing applied to as-drawn filamentary wires in a GlidCop and/or Cu sheath made by the internal magnesium diffusion process. Critical currents of as-drawn and isostatically pressed wires at high pressures up to 2.0 GPa followed by heat treatment at 640 °C for 40 min were measured. The obtained results show an improvement in boron powder density resulting in an increase of the critical current of MgB2 layers. The engineering current density increases by 4–13 times after the high-pressure treatment, and is influenced by the density of the boron powder and by the mechanical strength of the outer sheath.